2021
DOI: 10.3390/ijerph18073766
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Commercially Available Alcohol-Based Hand Rubs Formulated with Compliant and Non-Compliant Ethanol

Abstract: The COVID-19 pandemic led to panic-buying of alcohol-based hand rubs (ABHRs). In response, governmental agencies (e.g., Health Canada) permitted the sale of ABHRs formulated with “technical-grade” ethanol to alleviate the growing demand. Technical-grade ethanol contains elevated concentrations of impurities (e.g., acetaldehyde, etc.), which may exhibit dose-dependent toxicity. In this study, a rapid solvent extraction was employed to analyze gelled ABHRs via gas chromatography with flame ionization detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Other contaminants encountered were ethyl acetate, isobutanol, 1-propanol and 3-methyl-butanol [19]. In contradistinction, a Canadian study, found that all samples analyzed except one complied with alcohol content and methanol limits while 26 % did not comply with acetaldehyde levels [14].…”
Section: Quality Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other contaminants encountered were ethyl acetate, isobutanol, 1-propanol and 3-methyl-butanol [19]. In contradistinction, a Canadian study, found that all samples analyzed except one complied with alcohol content and methanol limits while 26 % did not comply with acetaldehyde levels [14].…”
Section: Quality Parametersmentioning
confidence: 99%
“…Ideally, methanol content is determined by spectrophotometry or gas chromatography techniques [13]. Low quality raw materials may contribute to unacceptable impurity profiles in the final product with respect to contaminants which in addition to methanol may include benzene, acetaldehyde, acetal and ethyl acetate [14][15][16][17]. Thus, the use of specific methods is necessary in ABHS analysis to accurately determine alcohol content, purity and exclude substitution or contamination with non-permitted alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heavy demand for hand sanitizers coupled with shortages of raw materials such as ethanol, use of industrial-grade alcohols was permitted interim in many countries. Hand sanitizer manufacturers used different feedstock that affected the quality of the end products and the type of impurities they contain ( Tse et al, 2021 ). Besides methanol and acetaldehyde, some volatile organic compounds (VOCs) such as benzene have been found in hand sanitizers ( Valisure, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because alcoholic products are more powerful and compatible, faster to be applied, and cause fewer skin problems [1,2]. Alcoholic hand rub contains mainly ethanol, isopropyl alcohol, or their combinations [3]. The use of alcohol for hand disinfection has received much attention in the community.…”
Section: Introductionmentioning
confidence: 99%